2010
DOI: 10.1038/clpt.2010.172
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efavirenz Autoinduction and Its Effect on Plasma Exposure in HIV Patients

Abstract: We investigated the influence of gender and pharmacogenetic variations on long-term efavirenz autoinduction and disposition among patients with HIV in Tanzania (N = 129). Plasma concentrations (at 16 h) of efavirenz and 8-hydroxyefavirenz were quantified at weeks 4 and 16 of therapy. Genotyping was performed to identify cytochrome P450 (CYP) 2B6*6, CYP3A5*3, *6, and *7, and ABCB1-3435 C/T genotypes. There were reductions in the median efavirenz concentration (Wilcoxon matched-pair test P < 0.001) and efavirenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
122
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 34 publications
(46 reference statements)
5
122
0
Order By: Relevance
“…However, patients with a large increase in clearance within the study period showed relatively low steady-state efavirenz concentrations, with some showing subtherapeutic concentrations on day 14. This finding correlates with the finding of Ngaimisi et al of subtherapeutic efavirenz concentrations in Tanzanian patients after 16 weeks of treatment [32], which was related to autoinduction and CYP2B6 polymorphism. This finding suggests that autoinduction exposes a few individuals to a risk of virological failure among populations previously known for high plasma concentrations and adverse effects of efavirenz.…”
Section: Discussionsupporting
confidence: 81%
“…However, patients with a large increase in clearance within the study period showed relatively low steady-state efavirenz concentrations, with some showing subtherapeutic concentrations on day 14. This finding correlates with the finding of Ngaimisi et al of subtherapeutic efavirenz concentrations in Tanzanian patients after 16 weeks of treatment [32], which was related to autoinduction and CYP2B6 polymorphism. This finding suggests that autoinduction exposes a few individuals to a risk of virological failure among populations previously known for high plasma concentrations and adverse effects of efavirenz.…”
Section: Discussionsupporting
confidence: 81%
“…Our ability to attribute efavirenz concentration changes to a genetic interaction modulating a minor elimination pathway was likely limited by sample size. However, formation of 7-OH efavirenz by CYP2A6 may have a more significant effect on plasma efavirenz concentrations during chronic dosing due to induction of CYP2A6, particularly in those subjects with slow CYP2B6 metabolizer phenotypes who do not exhibit induction of CYP2B6 activity (36)(37)(38). Consequently, some gene-gene interactions may be more prominent as efavirenz is dosed to steady state.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there may be a genetic susceptibility to the neurotoxic effects of EFV that is related to its rate of metabolism. Extensive EFV metabolizers have been identified that express the ‫1/1ء‬ haplotype of CYP2B6 (Ngaimisi et al, 2010). Thus, a genetic susceptibility in some individuals may exaggerate the neurotoxic effects of EFV because of a rapid metabolism of EFV with accumulations of the 8-OH-EFV metabolite.…”
Section: Discussionmentioning
confidence: 99%